Formação continuada de professores de Língua Portuguesa à luz do letramento: reflexões e proposta - Lima, Augusto José Savedra (2019)
This dissertation deals with the continued development of Portuguese language teachers, in dialogue with the literacy theory, and it’s a consequence of the research carried out in the Professional Master's Degree in Technological Teaching - MPET, at the Federal Institute of Education, Science and Technology of Amazonas - IFAM / Campus Manaus Centro - CMC. The research had as general objective to investigate in which narrative aspects of Portuguese Language teachers reflect their practices as agents of literacy. Thus, this work had four unfolding, the specific objectives: understanding the practices of Portuguese language teachers from their narratives; discussing the conceptions of Portuguese language teachers about literacy based on their narratives; identifying in the narratives of Portuguese Language teachers practices as agent of literacy; and elaborating a proposal of continued development for Portuguese Language teachers in the light of the literacy. To reach these goals, Oral History was chosen as a methodological way, using the participants' narratives in order to generate the data, based on interviews recorded and directed by a general script and individual scripts. Thus, in the data analysis process, four categories wich were divided in subcategories: a) profile of the Portuguese Language teacher of the Federal Institute of Education, Science and Technology of Amazonas - IFAM / Campus Parintins - IFAM CPA; b) practices and conceptions of the participants of the research regarding teaching-learning of reading and writing; c) practices as a literacy agent; and d) continued development in the light of literacy. The results evidenced: the concern of the participants in a continued development, because they understand the dynamism of the teaching; the attention to the plans and strategies devised for the classroom; the meaning given by them to the teacher's practice; your mobilizing capacity to organize spaces to carry out their activities; and the reflection they do about their pedagogical work. They also pointed out the teaching knowledge, research and reflection as development possibilities for these professionals, considering the theories about the continued development of teachers, literacy and textual / discursive genres. According to the theoretical basis of this work, the research course and its results, the educational product was built, a development course entitled Continued development for Portuguese language teachers: reflections and a proposal in the light of literacy, in digital format - e-book, which is structured in a review of the literature, basic texts to experience the development process, suggested scripts for development meetings and narratives of those who experienced the test process for product implementation.